Editorial: news and views from the RAFE - Marette, Stéphan; Le Velly, Ronan (Review of agricultural, food and environmental studies, 2020)
It is a great pleasure to write this editorial to present the new section in the Review of Agricultural, Food and Environmental Studies (RAFE) with the heading “News and Views” that should now appear regularly. This event also gives us the opportunity to take another look at the new editorial project, which has been implemented for 2 years now, leading to some remarkable results, notably in the recent publication of two special issues.